Bacterial septicemia in neonates - lbrahim, Aida H. (Journal of the Faculty of Medicine Baghdad, 2005)
Summary:Background: This study was conducted to isolate and identify the bacterial isolates of neonatal septicemia in a Neonatal Intensive Care Unite in the Baghdad teaching hospital and the resistance of these locally isolates to different antibiotics. Suspected cases of neonatal sepsis which were not treated with any antibiotics were enrolled.Methods: One to two milliliter of blood specimens were collected from these neonates aged from 3-7 days and cultured in Brain heart infusion broth.Results: Out of 90 neonates, 15 ( 15.5%) were positive on blood cultures. Results showed that nine isolates have been obtained belonging to Klebsiella spp. comprising (60%) out of the total isolates followed by Staphylococcus aureus (27.7%) and E coli (13.3%).Depending on these results, all isolates from neonates possessed high resistance against Penicillin, Ampicillin and Gentamicine, but were sensitive to Cefotaxime, Ciprofloxacin and Amikacin.Of the 15 cases four died only.Conclusion: I concluded from this study that the Gram negative bacteria especially Klebsiella spp (nonsocial al pathogen was a major pathogen especially among premature neonates.